A Content Analysis of Risk Management Disclosures in Canadian Annual Reports - Lajili, Kaouthar; Zéghal, Daniel (Canadian journal of administrative sciences, 2005)
This research paper examines risk information disclosures in Canadian annual reports to provide insights into the current risk disclosure environment, its characteristics, and the analytical usefulness of the information disclosed to the firm's stakeholders. Following a content analysis, the authors describe and then analyze in greater detail the subject matter of risk disclosures of TSE 300 Canadian companies by summarizing and classifying disclosed risk‐related information. Results show a high degree of risk disclosure intensity reflecting both mandatory and voluntary risk management disclosures. However, the analytical power of such disclosures, as captured by the risk assessment analysis, appears to lack uniformity, clarity, and quantification, thus potentially limiting their usefulness. The authors conclude that more formalized and comprehensive risk disclosures might be desirable in the future to effectively reduce information asymmetries between management and stakeholders. Résumé La présente étude analyse les divulgations d'informations sur le risque dans les rapports annuels canadiens. Elle se propose de jeter une lumière sur l'environnement actuel de divulgation des risques, ses caractéristiques, et l'utilité analytique des informations divulguées pour les acteurs de l'industrie canadienne. Grâce à la méthode de l'analyse du contenu, les auteurs décrivent puis analysent de faĉon plus détaillée le contenu actuel des divulgations d'informations sur le risque des entreprises du TSE 300. Ils y parviennent en synthétisant et en catégorisant les informations divulguées. Les résultats montrent que les divulgations se font à une fréquence assez élevée, consécutive aux divulgations obligatoires et volontaires de gestion des risques. Cependant, vu la manière dont l'analyse d'évaluation des risques divulgue ces informations, leur pouvoir analytique semble manquer d'homogénéité, de clarté, et de quantification, ce qui limite potentiellement leur utilité. Les auteurs concluent qu'à l'avenir, les divulgations de risques gagneraient à être plus formalisées et plus complètes. Ceci permettrait de réduire l'asymétrie des informations entre les gestionnaires des risques et les investisseurs.